Narrative Identity Reconstruction as Adaptive Growth During Mental Health Recovery: A Narrative Coaching Boardgame Approach - Kerr, Douglas J. R.; Deane, Frank P.; Crowe, Trevor P. (Frontiers in Psychology, 2019)
Objective: The purpose of this paper is to construct a conceptual framework for use in investigating the reconstruction of narrative identity as a key task in mental health recovery. Method: A selective integrative review of the theoretical and empirical literature relevant to narrative identity reconstruction in recovery was conducted. Sources included books, dissertations, internet resources, and professional journals. Findings: Together the topics reviewed provide a conceptual framework that offers an enriched understanding of how narrative identity reconstruction in recovery may be conceptualised and facilitated. Conclusions and Implications for Practice: The conceptual framework operationalised in a serious health boardgame (narrative identity coaching tool) is a way of integrating the various concepts and theories as discussed in the review. In practice, mental health professionals could use the game to engage their clients in recovery, offer a model of adaptive change that normalises the often irregular and uncertain journey of recovery, assist clients to build skills to reconstruct their preferred narrative identity, and foster their hope for a journey towards well-being and the fulfilment of their potential. A research direction is to explore what aspects of narrative identity and nonlinear dynamic processes of change are most important in people’s recovery narratives.